Transforming Primary Educators’ Leadership in the 21st Century: The Mediating Role of AI Self-Efficacy on the Relationship between Digital Growth Mindset and Teacher Leadership - Rizki Amelia; Suyono Suyono; Oktaviani Adhi Suciptaningsih; Wiku Aji Sugiri (International Journal of Educational Narratives, 2026)
Background. The integration of artificial intelligence in the basic education ecosystem demands the active role of educators as agents of change. However, the effectiveness of teachers’ leadership in technology adoption is highly dependent on their cognitive readiness and self-confidence in dynamic digital tools. Purpose. This quantitative research aims to examine the influence of Digital Growth Mindset (DGM) on Teacher Leadership (TL) in the AI era, as well as analyze the mediating role of AI Self-Efficacy (AISE) in this relationship. This study seeks to explore the pathways through which individual mindsets associate with collective leadership behaviors. Method. This study involved 288 primary school educators in Indonesia, predominantly situated in rural and district areas, selected through purposive sampling techniques. Data were collected using a structured questionnaire that measured DGM, AISE, and TL. Data analysis was carried out using the Structural Equation Modeling approach based on Partial Least Squares (PLS-SEM) to test the hypothesis of direct and indirect effects. Results. The findings show that Digital Growth Mindset has a substantial and significant direct effect on AI Self-Efficacy (  = 0.752, p < 0.001), but has a small direct effect on Teacher Leadership (  = 0.252, p = 0.001). Furthermore, AI Self-Efficacy proved to be a significant mediator bridging the influence of DGM on TL (  = 0.417, p < 0.001). This confirms that a developing mindset alone is not enough to encourage teacher leadership without strong technical confidence. Conclusion. This study makes a theoretical contribution by highlighting AISE as a critical mediating pathway linking cognition and the professional actions of educators. Practically, educational institutions are advised to prioritize professional development programs that not only instill a digital mindset, but also build technical self-efficacy through peer mentoring to ensure the success of systemic digital transformation in schools.